Application of Open Ended Approach in FPB and KPK Material in Grade 4 Elementary School Students - Silvia Farida; Feny Rita Fiantika; Susi Hermin Rusminati (Formosa Journal of Sustainable Research, 2023)
This study aims to determine the effect of an open ended approach on the critical thinking skills of grade IV elementary school students. This study used a quasi-experimental design quantitative research approach with a Posstest Only Control Group Design design. The sampling technique in this study was a saturated sample, namely the entire fourth grade students of SD Hang Tuah 10 Juanda. Data collection applies test, observation, and documentation methods. The test results through the calculation process are then analyzed through hypothesis tests by applying two-party t-tests starting with prerequisite tests in the form of normality tests and homogeneity tests. The results of this study show that = 2.6 and = 2.1 so that > or < with a significant level of 5% are rejected. This means that there is an influence of an open ended approach on the critical thinking skills of grade IV elementary school students